2006
DOI: 10.1021/ac060765a
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Quantifying and Visualizing Polyelectrolyte Multilayer Film Formation on Particles

Abstract: Colloidal particles prepared by using the layer-by-layer technique are increasingly finding application in diagnostics, drug delivery, and sensing. Herein, we outline methods for applying three established techniques, confocal laser scanning microscopy (CLSM), flow cytometry, and differential interference contrast (DIC) microscopy, to characterize ultrathin films of poly(styrenesulfonate) (PSS) and poly(allylamine hydrochloride) (PAH) assembled on silica particles. Both CLSM and flow cytometry require the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 26 publications
5
63
0
Order By: Relevance
“…Although the zeta potential profile in Figure 2A is consistent with layer-by-layer film growth, we note that these results could also arise from the iterative displacement (or stripping) of adsorbed layers of polymer or DNA from particle surfaces by an oppositely charged species upon exposure to each subsequent polyelectrolyte solution [56]. To further confirm layer-by-layer film growth, we characterized increases in the fluorescence intensities of film-coated particles during the assembly of films fabricated using fluorescently labeled DNA.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Although the zeta potential profile in Figure 2A is consistent with layer-by-layer film growth, we note that these results could also arise from the iterative displacement (or stripping) of adsorbed layers of polymer or DNA from particle surfaces by an oppositely charged species upon exposure to each subsequent polyelectrolyte solution [56]. To further confirm layer-by-layer film growth, we characterized increases in the fluorescence intensities of film-coated particles during the assembly of films fabricated using fluorescently labeled DNA.…”
Section: Resultsmentioning
confidence: 69%
“…These techniques cannot generally be used to characterize the growth of films assembled on the surfaces of colloidal microparticles [56]. However, past studies have demonstrated that changes in the zeta potentials of particles (e.g., as should occur after the adsorption of a negatively charged polymer or a positively charged polymer to the surface of a microparticle) can be used to characterize film growth and assembly [43, 5659]. Figure 2A shows representative changes in the zeta potentials of particles during the fabrication of a polymer/DNA film 2.5 bilayers thick.…”
Section: Resultsmentioning
confidence: 99%
“…The permeability of the film is low [42] and the mass of the multilayer increases linearly with the number of bilayers. [43] In PDDA/PSS system, the grooves and holes spread on the surface of film and the multilayer is loose. It is favorable for the permeation of polyelectrolyte molecules and the formation of an exponentially-growing multilayer, through the polyelectrolyte diffusing ''in'' and ''out of'' the film.…”
Section: Growth Regime Of Pah/pss and Pdda/pss Multilayersmentioning
confidence: 99%
“…In some instances it is possible to distinguish inter-crystalline interfaces due to differences in refractive indices between crystals. [31][32][33] Photomicrographs, shown in Figure 8, were taken at the highest magnification (~1000x) and the 20 μm bar in the lower left micrograph is representative for all photos. At the highest pressures, usually TATB crystals are no longer identifiable due to surface damage and flow.…”
Section: Pressing Characteristicsmentioning
confidence: 99%